Introduction of an Effective Method for Separating Conjugating Pairs of Paramecium - Yang, Xianyu; Xin Gao (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2019)
For the studies on the ciliate conjugation, it is indispensable to prepare a large number of conjugating (mating) pairs. In the last twenty years, we have done some studies on the conjugation of several species of Paramecium, and an effective method for separating mating pairs of Paramecium has been established, which will be introduced here.